Financial Repression in the European Sovereign Debt Crisis - Becker, Bo; Ivashina, Victoria (Review of Finance, 2018)
Abstract At the end of 2013, the share of domestic government debt held by the banking sectors of Eurozone countries was more than twice the amount held in 2007. We show that these increased bond holdings generated a crowding out of corporate lending. We find that the corporate loan supply was depressed by domestic sovereign bonds exclusively during the crisis period (2010–11). The crowding-out pattern holds across firms with different relationship banks within a given country. These findings suggest that sovereign bond holdings negatively impact private capital formation and reflect financial repression. We show that direct government ownership, as well as government influence through banks’ boards of directors, is among the channels used to influence banks.